2022
DOI: 10.3389/fonc.2022.988458
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition classification of circulating tumor cells predicts clinical outcomes in progressive nasopharyngeal carcinoma

Abstract: BackgroundLiquid biopsy facilitates the enrichment and isolation of circulating tumor cells (CTCs) in various human cancers, including nasopharyngeal carcinoma (NPC). Characterizing CTCs allows observation of the evolutionary process of single tumor cells undergoing blood-borne dissemination, such as epithelial-mesenchymal transition. However, the prognostic value of phenotypic classification of CTCs in predicting the clinical outcomes of NPC remains poorly understood.Patients and methodsA total of 92 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Our previous study indicated that dissociated NPC cells in the circulation exhibiting EMT/CSCs features were endowed with their metastatic potentials 61 . CTCs can be used for tumor stage determination and prognosis prediction of NPC at all stages, and especially epithelial/mesenchymal (E/M) hybrid CTCs predict adverse outcomes 110 , 111 . To be more exhilarating, a study showed that CTCs can be a novel more sensitive biomarker for minimal residual disease (MRD) of NPC patients 112 .…”
Section: Npc As Invasive Species and Its Metastasis As An Ecological ...mentioning
confidence: 99%
“…Our previous study indicated that dissociated NPC cells in the circulation exhibiting EMT/CSCs features were endowed with their metastatic potentials 61 . CTCs can be used for tumor stage determination and prognosis prediction of NPC at all stages, and especially epithelial/mesenchymal (E/M) hybrid CTCs predict adverse outcomes 110 , 111 . To be more exhilarating, a study showed that CTCs can be a novel more sensitive biomarker for minimal residual disease (MRD) of NPC patients 112 .…”
Section: Npc As Invasive Species and Its Metastasis As An Ecological ...mentioning
confidence: 99%
“… 23 This may be due to the acquisition of mesenchymal properties by tumor cells through EMT, which includes characteristics such as loss of cell polarity, reduced cell adhesion, induced cell migration, and increased intravascular permeability, significantly contributes to the progression and metastasis of malignant tumors. 29 , 30 Remarkably, mesenchymal-type CTCs exhibit enhanced invasiveness due to their acquisition of mesenchymal phenotypic traits. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 Remarkably, mesenchymal-type CTCs exhibit enhanced invasiveness due to their acquisition of mesenchymal phenotypic traits. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…The CanPatrol™ CTC enrichment technique (SurExam, Guangzhou, China) was performed on peripheral blood samples to isolate and classify CTCs as previously described [ 10 , 11 ]. A 5-mL peripheral blood sample was collected using EDTA-anticoagulated blood collection tubes and mixed upside down.…”
Section: Methodsmentioning
confidence: 99%
“…The CanPatrol™ assay system (SurExam, Guangzhou, China) [ 10 , 11 ] is a second-generation CTC enrichment technology based on immuno-removal combined with nano-filtration. It does not rely on specific antibody capture and has a removal efficiency of > 99.97% for leukocytes and a recovery rate of > 80% for tumor cells.…”
Section: Introductionmentioning
confidence: 99%